Correction to: ZIKA virus elicits P53 activation and genotoxic stress in human neural progenitors similar to mutations involved in severe forms of genetic microcephaly. Issue 12 (December 2018) - El Ghouzzi, Vincent; Bianchi, Federico; Molineris, Ivan; Mounce, Bryan; Berto, Gaia; Rak, Malgorzata; Lebon, Sophie; Aubry, Laetitia; Tocco, Chiara; Gai, Marta; Chiotto, Alessandra; Sgrò, Francesco; et al.
The authors wish to point out that the name of the first author is appearing incorrectly on Pubmed: it should be El Ghouzzi V (and not Ghouzzi VE). In addition, the words "and p53" appear at the end of the title in the original publication (https://www.nature.com/articles/cddis2016266 ) and in the previous erratum version (https://www.nature.com/articles/cddis2016446 ). This is not correct.